State of telemedicine use in pediatric surgery in the USA-where we stand and what we can gain from the COVID-19 pandemic: a scoping review - Gregory Metzger; Kris Jatana; Jordan Apfeld; Katherine J Deans; Peter C Minneci; Ihab Halaweish (BMJ Publishing Group, 2021)
Background Within the last decade, the use of telemedicine within in primary care in the USA has greatly expanded; however, use remains uncommon in surgical specialties. The spread of Coronavirus disease 2019 (COVID-19) prompted healthcare institutions to limit in-person contact, resulting in an increase in telemedicine across all specialties, including pediatric surgery. The aims of this review were to evaluate potential barriers that limited the use of telemedicine in pediatric surgery prior to the COVID-19 period and to define how best to incorporate its use into a pediatric surgical practice going forward.Methods A scoping review was performed to identify gaps in the literature pertaining to the use of telemedicine within general pediatric surgery in the USA prior to the outbreak of COVID-19. Next, a focused evaluation of the legislative and organizational policies on telemedicine was performed. Lastly, findings were summarized and recommendations for future research developed in the context of understanding and overcoming barriers that have plagued widespread adoption in the past.Results Despite evidence of telemedicine being safe and well received by adult surgical patients, a total of only three studies representing original research on the use of telemedicine within pediatric surgery were identified. Legislative and organizational policies regarding telemedicine have been altered in response to COVID-19, likely resulting in an increase in the use of telemedicine among pediatric surgeons.Conclusions Telemedicine offers a safe and effective option for patients seeking an alternative to the in-person clinic appointment. The increased utilization of telemedicine during the COVID-19 pandemic will provide an opportunity to learn how best to leverage the technology to decrease disparities and to overcome previous barriers.